Food and social identity: Rural lives that appear through food - Nicolodi Francescato RUIZ, Eliziane; Engel GERHARDT, Tatiana (Revista de Nutrição, 2023)
Objective The objective was to analyze the interactions between food and identity by exploring the daily food eaten by a rural community. Under the gift theory view, the aim is to present readings concerning a rural identity that the research participants constituted through eating; this aim is premised on the assumption that analyzing the relationship between the identity of a group and eating becomes important because of the marked infl uence that belonging to a collective has in food. Methods An ethnographic approach was used including participant observation, fi eld diary annotations, and interviews with 21 interlocutors. Results The activity of eating produced at least two categories that characterized rural identity: one marked by the stigma of the past, and the other by values that, above all, denote a reaction to stigma; a reaction to stigma is linked to the work that also sustains the honor of a family, the consumption of food/goods common in the city, inclusion in a larger society, and commitment to the collective. Conclusion Eating, in addition to the biological and individual, can also be apprehended as a complex and revealing sociocultural phenomenon, including ways of belonging to a group. With food a marked rural identity appears, mainly through reactions to stigmata.